DETERMINANTS OF TRANSFER PRICING - Nia Anggraeni; Novrida Qudsi Lutfillah (Journal of Management and Business, 2019)
Transfer pricing is an effort to minimize the tax burden by allocating corporate profits to the relations company with lower tax rates. This research aimed to analyze the effect of corporate governance, tunneling incentive and sales growth to practices transfer pricing. Quantitative method and secondary data of annual report. The populations in this research are manufacturing company sector basic and chemical industrial listed on the Indonesia Stock Exchange (BEI) for years 2014-2017 totaling 13 sample companies selected by purposive sampling method.The analysis technique data used is a binary logistic regression.The results of this research indicates that the variable corporate governance and sales growth not effect on practice transfer pricing, while tunneling incentive positive effect on practice transfer pricing.